Libertés et contraintes dans les actes de femmes dans le tabellionnage de Caen (2e moitié du XVe siècle) - Denise Angers (Tabularia)
Caen’s legal records contain thousands of contracts involving women, either as primary or secondary participants. Most of the time the style of these contracts is dry: they contain no information about daily life in Caen. Yet  some contracts can be more descriptive than others and allow the motivations and feelings of the contractors to come through. Two of such contracts are particularly interesting: they reveal women’s concern for their lineage despite having no children. One is Perrette Lanquetil’s will and the other is an agreement signed between Jeanne de Neufmers and a blood relative.